Effect of DPP-4 inhibitor sitagliptin against ischemia-reperfusion (I/R) injury in hyperlipidemic animals - Al-awar, Amin; Almási, Nikoletta; Szabó, Renáta; Ménesi, Rudolf; Szűcs, Gergő; Török, Szilvia; Pósa, Anikó; Varga, Csaba; Kupai, Krisztina (Acta Biologica Szegediensis, 2019)
Hyperlipidemia is a major risk factor associated with increased risk of myocardial infarction. Dipeptidyl peptidase-4 (DPP-4) inhibitors such as sitagliptin are a class of oral anti-diabetic drugs with secondary pleiotropic effects on metabolic and cardiovascular parameters. This study aimed to determine the possible cardioprotective effects of sitagliptin on ischemia-reperfusion (I/R) injury in animals kept on high-fat diet. Male Wistar rats were fed with high-fat diet (HF) for 12 weeks, to induce hyperlipidemia. During the last two weeks of the feeding period, animals were orally treated with different doses of sitagliptin (Sitg: 25, 50, 100, and 150 mg/kg/day), or saline as a control. Heart tissues were then isolated and subjected to two different I/R-injury protocols for infarct size (IS) measurement and biochemical analysis. To test the role of NOS enzyme, NOS inhibitor (L-NAME) was injected intraperitoneally for IS evaluation. As an effective dose, Sitg (50 mg) exhibited a significant impact on IS. NOS activity increased significantly in the Sitg (50 mg) treated groups; however this protective effect was abolished in the presence of L-NAME. The protective effect of Sitg that was mediated by TRP channels in our previous study on normolipidemic animals was abrogated in animals fed with high-fat diet.